Політична активність молоді як чинник становлення незалежності - Каретна, Ольга Олександрівна; Каретная, Ольга Александровна; Karetnaja, О. (My University, 2013)
The article is about forming and realization of public youth policy in Ukraine where on a background the general tendencies of democratization of society, takes place increases of young people role and at the same time expansion of possibilities for socialization and individual development of personality, increase of value of partnership principle in relationship-building of the state and other subjects of social action, in particular to the young people.
Каретна О. О. Політична активність молоді як чинник становлення незалежності / О. О. Каретна // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 208-217.
Keywords: державна молодіжна політика в Україні; роль молоді в демократизації суспільства в Україні; соціалізація та індивідуальний розвиток особистості; принцип партнерства в побудові стосунків держави і молоді; государственная молодежная политика в Украине; роль молодежи в демократизации общества в Украине; социализация и индивидуальное развитие личности; принцип партнерства в построении отношений государства и молодежи; state youth policy in Ukraine; the role of youth in the democratization of society in Ukraine; socialization and individual development; the principle of partnership in building relations between the state and youth